2019
DOI: 10.1128/mbio.00216-19
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Plasticity in a Sulfur-Oxidizing Marine Bacterium from the SUP05 Clade Enhances Dark Carbon Fixation

Abstract: Sulfur-oxidizing bacteria from the SUP05 clade are abundant in anoxic and oxygenated marine waters that appear to lack reduced sources of sulfur for cell growth. This raises questions about how these chemosynthetic bacteria survive across oxygen and sulfur gradients and how their mode of survival impacts the environment. Here, we use growth experiments, proteomics, and cryo-electron tomography to show that a SUP05 isolate, “Candidatus Thioglobus autotrophicus,” is amorphous in shape and several times larger an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 49 publications
2
55
0
Order By: Relevance
“…In some habitats, they will encounter sulfide. The sulfur cycle is generally coupled with the carbon cycle (46)(47)(48); however, it is still unclear how sulfide affects Synechococcus spp. and how they deal with it.…”
mentioning
confidence: 99%
“…In some habitats, they will encounter sulfide. The sulfur cycle is generally coupled with the carbon cycle (46)(47)(48); however, it is still unclear how sulfide affects Synechococcus spp. and how they deal with it.…”
mentioning
confidence: 99%
“…Like other SUP05 cells, those associated with the tentacles of O. pearseae were small (~500 nm in diameter; Shah et al 2019). Presumably these symbionts require both oxygen and sulfide near simultaneously, for example "Candidatus Thioglobus autotrophicus", a member of the SUP05 group, has an aerobic phenotype, and uses sulfide while respiring oxygen (Marshall and Morris 2013;Shah et al 2019). In this regard, it would be reasonable to house bacteria as close to the tissue surface as possible in order to accommodate gas exchange and meet symbiont metabolic demands.…”
Section: Bacterial Community Analysis Of Ostiactis Pearseae From the mentioning
confidence: 86%
“…Additionally, the epidermis in Anthozoa can function in nutrition (Fautin & Mariscal 1991), even more so than the gastrodermis, through direct uptake of dissolved organic compounds (Schlichter 1975(Schlichter , 1980, thus the positioning of nutritional bacteria in the epidermis may increase effective exchange of small molecules. Like other SUP05 cells, those associated with the tentacles of O. pearseae were small (~500 nm in diameter; Shah et al 2019). Presumably these symbionts require both oxygen and sulfide near simultaneously, for example "Candidatus Thioglobus autotrophicus", a member of the SUP05 group, has an aerobic phenotype, and uses sulfide while respiring oxygen (Marshall and Morris 2013;Shah et al 2019).…”
Section: Bacterial Community Analysis Of Ostiactis Pearseae From the mentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3. First, Shah et al (Shah et al, 2019) described the comparative proteomic analysis of a marine sulfur-oxidizing isolate, 'Candidatus Thioglobus autotrophicus', grown under oxic versus anoxic conditions with varying levels of sulfur availability. The authors analysed biological triplicates and identified peptides using a Q-Exactive HF tandem mass spectrometer following a 145-min reverse-phase gradient.…”
Section: Introductionmentioning
confidence: 99%